MNCs, Worker Identity and the Human Rights Gap for Local Managers - Millar, Carla C. J. M.; Choi, Chong Ju (2010)
This article analyses MNCs, worker identity and the ethical vulnerability caused by over-reliance on expatriate managers and under-reliance on local managers, who are often undervalued. It is argued that MNCs not only need but also have an obligation to assess local managers’ knowledge and contributions as having not only operational and market values, but also institutional value. Local managers both give access to and form part of local social capital and the treatment they receive is an element in the CSR performance of the MNCs. Recognition of the value of equal treatment creates an ethical imperative that the barriers of cultural difference be overcome. We see such an approach towards local managers as more fully taking into account the human rights of these local managers. Such a holistic approach is increasingly relevant for MNCs in the 21st century, as MNCs increasing globalize into new large emerging markets such as Brazil, Russia, India and China.
Keywords: Psychic distance; Institutions; Globalisation; Human Rights; Worker identity; MNCs